Essays on international risk sharing : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Economics at Massey University, Palmerston North, New Zealand - Rana, Faisal (Massey University, 2013)
One of the most important benefits of financial integration in theory is the international risk sharing opportunity it provides by insuring income and consumption against domestic output fluctuations. Since sharing risk among countries can yield large potential gains, it is crucial to have a deeper understanding of the channels through which risk sharing takes place at the county level. This thesis attempts to deepen the understanding of the channels of risk sharing in the existing body of knowledge. The first empirical study examines the potentially important role of migrants’ remittances in income risk sharing. Using a large sample of 86 developing countries for the period 1990 2010 the results suggest that remittance inflows serve as an effective channel through which output fluctuations are being absorbed. The diversification of migrants turns out to be the leading explanation of the cross-country differences in the extent of risk sharing: the more diverse the migration destinations of a country, the greater the amount of risk shared. The second empirical study contributes to the literature by simultaneously examining the cross-sectional and intertemporal channels of risk sharing among states of Australia and regions of New Zealand. In doing so, it investigates the viability of a currency union between Australia and New Zealand from a risk sharing perspective. The results show that the extent of intertemporal smoothing is negligible in both countries. The study also finds a virtual absence of risk sharing when Australia and New Zealand face negative aggregate fluctuations, raising doubts about the feasibility of the union, particularly during economic downturns. From the methodological viewpoint, the study shows that it is possible to examine both interstate risk sharing and intertemporal smoothing mechanisms in a single framework; besides, distinguishing and measuring the extent of different types of shocks. Motivated by the concerns that the volatility of returns adversely affects the degree of risk sharing through international financial markets’ channel the third study explores the underlying factors that affect the volatility of returns on cross-border asset (equity and debt) holdings in a sample of 28 industrialized countries. Using aggregate portfolio data, it presents the first cross-country evidence on the leading determinants of the volatility of returns. The main findings are that greater portfolio concentration and an increase in asset holding in emerging markets lead to an elevation in the return volatility, whereas more financial integration and greater household share cause a reduction in the return volatility. The results indicate several possible ways to reap large potential gains from international risk sharing.
Keywords: Risk sharing; Financial integration; International risk sharing; International finance; Currency union